2009
DOI: 10.1007/s11269-009-9437-y
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the Optimal Allocation of Water Resources in a Saltwater Intrusion Area: A Case Study in Pearl River Delta in China

Abstract: This paper presents a model for the optimal allocation of water resources in saltwater intrusion areas. The model is comprised of four modules: a joint operation of river and reservoirs module (JORRM), a saltwater intrusion analysis module (SIAM), an economic analysis and in-stream ecology demand module (EAIEDM) and a water allocation module (WAM). Considering the social, economic and environmental aspects, the model has three objectives: the maximization of economic interest (OF 1 ), maximization of social sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(40 citation statements)
references
References 26 publications
(31 reference statements)
0
40
0
Order By: Relevance
“…Although the Datengxia hydro-engineering project is often considered as the necessity to alleviate severe salt intrusion problems (D. Liu et al, 2009), our result indicates that improved water management policy (MP strategy) is an additional option for policy makers to take up the challenge. First, as the latest key hydro-engineering project in the PRB, the Datengxia reservoir is expected to alleviate the salt intrusion damage by providing extra discharge for salt suppression in the estuary.…”
Section: Policy Implicationsmentioning
confidence: 83%
See 2 more Smart Citations
“…Although the Datengxia hydro-engineering project is often considered as the necessity to alleviate severe salt intrusion problems (D. Liu et al, 2009), our result indicates that improved water management policy (MP strategy) is an additional option for policy makers to take up the challenge. First, as the latest key hydro-engineering project in the PRB, the Datengxia reservoir is expected to alleviate the salt intrusion damage by providing extra discharge for salt suppression in the estuary.…”
Section: Policy Implicationsmentioning
confidence: 83%
“…The strategy to receive "extra supply" (ES) refers to the current government strategy that addresses severe salt intrusion with engineering projects(D. Liu, Chen, & Lou, 2009) . The strategy comprises the release of large amounts of freshwater from the upstream basin to the PRD when severe salt intrusion is projected to occur (Huang, 2009).…”
Section: Coping Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced low flow, in combination with rising sea levels, has caused severe saltwater intrusion in the delta (Li and Ao 2000). Increasing salinity poses a potential threat to water supply in the delta (Liu et al 2010). In a previous study, we showed that throughout the basin dry season rainfall and discharge are likely to reduce in the future due to climate change (Yan et al 2015).…”
Section: Problem Formulationmentioning
confidence: 86%
“…Moreover, it requires no continuity-differentiability on objective functions, and has a good performance in problems with discrete decision variables (Morshed and Kaluarachchi 2000). Many researchers have applied it to water allocation problems (Davijani et al 2016;Nouiri 2014;Elferchichi et al 2009;Zahraie and Tavakolan 2009;Liu et al 2010). The algorithm includes a random, parallel, and adaptive search procedure, based on the mechanics of natural selection that is utilized to search for the fittest solution to a problem with multiple objectives.…”
Section: ) Maximize Reservoir Storagementioning
confidence: 99%